Answer:
[tex]2x^2-x-6[/tex]
or
[tex]4x^2-21x-2[/tex]
Step-by-step explanation:
The difference of two trinomials [tex]P(x)[/tex] and [tex]Q(x)[/tex] is [tex]x^2 - 10x + 2.[/tex] This means that
[tex]P(x)-Q(x)=x^2-10x+2[/tex]
or
[tex]Q(x)-P(x)=x^2-10x+2[/tex]
If one of the trinomials is [tex]P(x)=3x^2-11x - 4,[/tex] then
[tex](3x^2-11x-4)-Q(x)=x^2-10x+2[/tex]
or
[tex]Q(x)-(3x^2-11x-4)=x^2-10x+2[/tex]
1. If [tex](3x^2-11x-4)-Q(x)=x^2-10x+2,[/tex] then
[tex]Q(x)=(3x^2-11x-4)-(x^2-10x+2)\\ \\Q(x)=(3x^2-x^2)+(-11x+10x)+(-4-2)\\ \\Q(x)=2x^2-x-6[/tex]
2. If [tex]Q(x)-(3x^2-11x-4)=x^2-10x+2,[/tex] then
[tex]Q(x)=(x^2-10x+2)+(3x^2-11x-4)\\ \\Q(x)=(x^2+3x^2)+(-10x-11x)+(2-4)\\ \\Q(x)=4x^2-21x-2[/tex]